Tata Kelola Keuangan berbasis Good Governance di Lembaga Pendidikan di MTs N 10 Banyuwangi - Al Hadi, Moh. Sabiq; Mu’arif, Syamsul (Instructional Development Journal, 2025)
Abstract: This study aims to describe Good Governance-Based Financial Governance in educational institutions, especially in MTs N 10 Banyuwangi, with a focus on transparent, accountable, and participatory financial management. Through a qualitative constructivist approach, this study explores how stakeholders such as principals, financial managers, teachers, and parents construct their realities related to financial management. The results of the study indicate that digitalization, such as the implementation of e-budgeting applications, accelerates the budget management process and improves data accuracy. However, challenges related to further training for financial managers are still needed to optimize the results of digitalization. In addition, this study also reveals that the implementation of Good Governance principles can function as a school branding tool by increasing public trust through transparency and accountability in the management of facilities and infrastructure. On the other hand, the challenges of integrating Good Governance in public schools, such as MTs N 10 Banyuwangi, include obstacles in unsystematic asset recording and bureaucracy that slows down facility maintenance. These findings indicate that although digitalization and Good Governance principles can improve efficiency, there are still obstacles in their implementation that affect the operation and image of the school.Abstrak: Penelitian ini bertujuan untuk menggambarkan Tata Kelola Keuangan Berbasis Good Governance di lembaga pendidikan, khususnya di MTs N 10 Banyuwangi, dengan fokus pada pengelolaan keuangan yang transparan, akuntabel, dan partisipatif. Melalui pendekatan kualitatif konstruktivisme, penelitian ini mengeksplorasi bagaimana para pemangku kepentingan seperti kepala sekolah, pengelola keuangan, guru, dan orang tua mengonstruksi realitas mereka terkait pengelolaan keuangan. Hasil penelitian menunjukkan bahwa digitalisasi, seperti penerapan aplikasi e-budgeting, mempercepat proses pengelolaan anggaran dan meningkatkan akurasi data. Namun, tantangan terkait pelatihan lebih lanjut bagi pengelola keuangan masih diperlukan untuk mengoptimalkan hasil digitalisasi. Selain itu, penelitian ini juga mengungkapkan bahwa penerapan prinsip Good Governance dapat berfungsi sebagai alat branding sekolah dengan meningkatkan kepercayaan masyarakat melalui transparansi dan akuntabilitas dalam pengelolaan sarana dan prasarana. Di sisi lain, tantangan integrasi Good Governance di sekolah negeri, seperti MTs N 10 Banyuwangi, mencakup kendala dalam pencatatan aset yang tidak sistematis serta birokrasi yang memperlambat pemeliharaan fasilitas. Temuan ini menunjukkan bahwa meskipun digitalisasi dan prinsip Good Governance dapat meningkatkan efisiensi, masih ada hambatan dalam implementasinya yang mempengaruhi operasional dan citra sekolah.